Assessment of cavitation and impingement effects of submerged water jet on Ti alloy surface. (April 2015) - Liu, H. X.; Shao, Q. M.; Kang, C.; Gong, C.
Abstract : An investigation is conducted to explore the effect of submerged water jet on solid material surface. With jet pressures ranging from 80 to 150 MPa, jet impingement on Ti-6Al-4 V samples is implemented experimentally. Experiments enable a quantitative evaluation of surface morphology features, residual stress and surface roughness associated with the impinged samples. A comparison is performed between submerged and non-submerged water jets. The results show that cavitation phenomenon manifests itself in submerged water jet as a ring-shape cavity zone, and the occurrence of cavitation is confirmed by the surface morphology features and local surface roughness on impinged surfaces. An almost linear relationship between residual stress and impingement time is corroborated. As for the resultant pits on impinged surfaces, smooth perimeters are caused by submerged water jets, while non-submerged water jets give rise to rather irregular pit perimeters along with comparatively powerful impingement force.